2020
DOI: 10.1109/tcomm.2020.2969416
|View full text |Cite
|
Sign up to set email alerts
|

LPD Communication: A Sequential Change-Point Detection Perspective

Abstract: In this paper, we establish a framework for low probability of detection (LPD) communication from a sequential change-point detection (SCPD) perspective, where a transmitter, Alice, wants to hide her signal transmission to a receiver, Bob, under the surveillance of an adversary, Willie. The new framework facilitates to model LPD communication and further evaluate its performance under the condition that Willie has no prior knowledge on when the transmission from Alice starts and that Willie wants to detect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…). Note that (28) differs from (13) in the sense that in (28), the signal matrices obtained in different time blocks are collected together to make a decision, while in ( 13), the decision is made based solely on the signal matrix obtained in a single time block.…”
Section: A Covertness Constraint Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…). Note that (28) differs from (13) in the sense that in (28), the signal matrices obtained in different time blocks are collected together to make a decision, while in ( 13), the decision is made based solely on the signal matrix obtained in a single time block.…”
Section: A Covertness Constraint Analysismentioning
confidence: 99%
“…Some recently efforts have been devoted to improving the covert communication performance. It has been revealed that by exploiting the adversary's uncertainty on the statistical information of its channel outputs, the covert communication performance can be greatly improved, and in some cases, non-vanishing covert communication rates exist, for example, when the adversary has uncertainty on its noise power [9], [10] or when the adversary is uncertain about the transmission time [11]- [13].…”
Section: Introductionmentioning
confidence: 99%
“…which is a convex SDP. Let W opt c,1 denote the optimal solution of problem (23). Due to relaxation, the rank of W opt c,1 may not equal to one.…”
Section: B Proposed Zero-forcing Beamformers Designmentioning
confidence: 99%
“…Next, we consider the design of w b . Let w opt c,1 denote the beamformer of problem (23). Then, let P c = w opt c,1 2 denote the transmission power of w opt c,1 .…”
Section: B Proposed Zero-forcing Beamformers Designmentioning
confidence: 99%
See 1 more Smart Citation